Understanding the Motives and Intention of Blood Donation during the Pandemic - Yusof, Junaidah; Ab Rahim, Sakinah; Mohd Noor, Sabariah; Panatik, Siti Aisyah; Wan Husin, Wan Nurul Izza; Bungsu, Mohd Sharial (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: In every country, an adequate and reliable blood supply can be assured by a stable base of regular, voluntary, and unpaid blood donors. However, with the strike of COVID-19 around the world, fewer donors have come forward to donate blood since the government’s movement control order. Therefore, to ensure the blood supply is always sufficient, this study discussed the Malaysians’ motivation and intention to donate blood during the COVID-19. MATERIALS AND METHODS: The structural focus group discussion was conducted among nine informants. The informants are classified into four groups, which are non, first-time, regular, and lapsed (repeated/occasional) blood donors. RESULTS: It indicated that the regular and lapsed group of blood donors were motivated by the satisfaction of donating blood. Meanwhile, first-time donors are motivated to donate blood because of extrinsic rewards. However, the donors attested that the movement control order restricted their movement to go to the blood transfusion center. On the other hand, the non-donor group admitted that they do intend to donate blood. Still, several factors such as work commitment, location, and fear of being infected by COVID-19, hold them from doing so. CONCLUSIONS: These findings will serve as insights for future blood donation disruption remediation, especially during unexpected situations, as well as the success of the Malaysian blood campaign.